Inter‐function anomaly analysis for correct SDN/NFV deployment. (18th December 2015) - Basile, Cataldo; Canavese, Daniele; Lioy, Antonio; Pitscheider, Christian; Valenza, Fulvio
Summary: Implementing the security of a network consists in individually configuring several network functions. Network functions are configured by means of a policy composed of a set of rules, but their actual behaviour is influenced by the other policies implemented by all the other network functions around them. This paper proposes a formal model that can be used to detect inter‐function anomalies, which are defined as the interferences between two or more functions deployed in the same network. We have proved with experiments that the proposed model is fast and scalable. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Inter‐function anomaly analysis refers to the detection of interferences between two or more functions deployed in the same network. The policy analyser is a new component added to the network function virtualization (NFV) architecture that implements a formal model for detecting inter‐function anomalies. It takes as input the virtual network function configurations and network service descriptors and returns the anomalies identified. The result of the analysis can be used directly by the NFV orchestrator or by the network administrator to reduce incoherences and service problems.